Knowledge, attitude, and awareness of biocompatibility of orthodontic materials among dental students - Shabbarish Chockalingam; Nivethigaa Balakrishnan (Wolters Kluwer Medknow Publications, 2022)
The aim of this study is to find the knowledge, attitude and awareness of biocompatibility of orthodontic materials among dental students.A survey of 13 questions was created using Google Forms. The questions on the survey cover a wide range of topics including the awareness of cytotoxicity of orthodontic materials, their corrosive potential, ways of preventing corrosion and release of subsequent substances, and various means by which these physiological actions occur. This survey was circulated among dental undergraduate students and the responses recorded were then transferred to SPSS software. Here we conducted descriptive analysis to produce a pie chart and Chi square test to determine the association and statistical significance.The results were noted and examined in the form of bar graphs. The p value for this study was found to be 0.01, which makes this study statistically significant. The awareness about the biocompatibility of orthodontic materials among dental students was found to be low. Continuing dental education programs can be conducted to constantly improve the knowledge regarding the judicious and ecofriendly use of all newly available dental materials.